Implementasi Kualitas Pelayangan pada PT Pos Indonesia Cabang Karawang - Ara Nopita; Sungkono S (Yayasan Daarul Huda Kruengmane, 2023)
The focus of this research is the Quality of Service at the Karawang Branch of the Indonesian Post Office. The purpose of this study was to find out how much the quality of service at the Karawang Branch of the Indonesian Post Office. However, in reality what researchers found in the field were delays in delivery, lack of facilities and infrastructure, and inadequate parking space. The research method used is quantitative using a questionnaire to collect customer and employee data. The results according to this study are to put information about service quality, so that the Karawang Branch of the Indonesian Post Office has a better image in the eyes of consumers, and also consumers are happier to use the services of the Karawang Branch of the Indonesian Post Office, so that the ultimate goal is to create customer satisfaction.